#Me(n)Too: Storying a Male-on-Male Sexual Assault. Issue 3 (3rd April 2019) - Purnell, David
Abstract: 1 An individual life is simultaneously flawed and valuable. All victims and survivors of sexual assault are unique, as are their stories. The culture of shame surrounding sexual assault on men shows victimization as a weakness. This attitude is sanctioned by the inherent gender inequality present within societies. These inequalities played a major role in my losing sight of my self-worth due to sexual assault, keeping myself in the darkness, and giving in to others' control of me causing the road to self-forgiveness to become a difficult journey to traverse. When toxic, masculinity and shame are harbored within one's self, an internal experience of unexpected exposure keeps us from trusting others. The shame creates a cloak of darkness and secretiveness. Instead of secrecy, we need space for men to tell their stories of sexual assault.